The prevalence and characteristics of fast food outlets in Ontario hospitals. Issue 9 (September 2015) - Harel, Z.; Goldberg, H.; Harel, S.; Cram, P.; Bell, C.M.
Highlights Fast food outlets can be found in almost two-thirds of hospitals in Ontario. Most of these outlets are coffee/donut chains (56%). Among 28 teaching hospital sites, 21 had a fast food outlet operating on their premises.